GEOMORPHOLOGY CHARACTERISTICS AND THE CROP PRODUCTION IN TEMPORARY PARANA STATE, BRAZIL - Franca Junior, Pedro [UNESP]; Casale Dalla Villa, Maria Estela (Univ Estadual Paulista Julio Mesquita Filho, 2015)
Parana is the major agricultural producers in Brazil, with a diversified agricultural agenda with morpho-pedological aspects, climatic conditions coupled with the use of advanced agricultural techniques, which place highlighted in terms of productivity. Based on these findings, checking Brazil and Parana and mappings based on the Atlas of the Agrarian Question of Brazil Girardi (2008), this paper aims to demonstrate through specific thematic maps the relationship between agricultural production of grain (2010) and geomorphological characteristics that affect these crops in the Parana state. In this research, we used sedated IBGE/SIDRA (2010) for agronomic information; the cartographic base of the IBGE (2010) and Phil Cartho5.72 program for interpolation of information and the generation of maps. From the incident maps production (Ton/Hec) developed a general map to spatialize the belts production temporary (corn, soybean and sugarcane) crops in Parana. Stood out 16 geomorphological units with favorable agricultural potential with a low vulnerability (weakness), well-developed soils, slopes and thin, which favors the mechanized and good agricultural practices.
Keywords: agricultural production of Parana; geomorphological units; thematic maps; productive corridor; weaknesses and environmental potential